(untitled) (International journal of artificial intelligence, 2025)
The emergence of Virtual Reality (VR) and Augmented Reality (AR) technologies has opened up new possibilities in modern education, particularly in language learning. This paper examines how integrating VR and AR can foster linguistic skills among learners by creating immersive, interactive, and authentic environments. By simulating real-life communication scenarios and enhancing context-based language exposure, these technologies provide learners with dynamic opportunities to develop core language competencies. The study explores the pedagogical advantages, technological challenges, and long-term potential of using VR and AR as tools to support language acquisition. Findings suggest that immersive technologies can significantly improve students’ engagement, motivation, and practical use of language in educational settings.